Taxes and fiscal policy in under-developed countries - United Nations (New York : United Nations Technical Assistance, 1954)
The report is designed to present the thinking which has developed out of the technical assistance and related efforts. It takes into account also contributions of economists and public finance specialists of different countries who are re-examining the conceptual framework of taxation and fiscal policy in under-developed economies.
Includes index
osc 3/7/17
Loans
Keywords: Taxation